ANALISIS PERSIAPAN DAN KESIAPAN KALIMANTAN TENGAH SEBAGAI PROPINSI PERCONTOHAN UNTUK MELAKSANAKAN UJI COBA PERCONTOHAN REDD+ DI INDONESIA - , NIZAR ARDHANIANTO, Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Government of the Republic of Indonesia and the Government of the Kingdom of Norway (Norway) formed a partnership on climate change through a memorandum of Cooperation/Letter of Intent (LoI) that focuses on REDD+. One of the follow up that which is laid down LOI Central Kalimantan province as a pilot to carry out a pilot trial during the early stages of reducing emissions from Deforestation and Forest Degradation (REDD+) in Indonesia. This research aims to gain a picture of the readiness of the Government of the province of Central Kalimantan Province as a pilot. The study also sought to find out what a priority aspects and criteria of the readiness of Central Kalimantan as a pilot area for implementing REDD+ based on perceptions of stakeholders in order to build shared understanding about the activities of the preparatory activities. Sampling methods used are purposive sampling with a tutor who includes, companies, academics, policy makers and the public. The sample is determined by using the snowball approach, where the next sample by sample previously nominated until it obtained a relative information. Methods of data analysis in this study using a method that combines explorative description of qualitative method using in depth interview to assess the readiness of Central Kalimantan province and quantitative measurement method using likert scale for through can know priority aspects and criteria of the readiness of Central Kalimantan province as a pilot. Based on the results of research and discussion has been done is the conclusion that in preparing the implementation of REDD+ in the province of Central Kalimantan, priority aspect that needs to be prepared is (1) Social Aspects of Economic dependence of the community, the rate of conversion of forest SDH, the level of need for land for the fulfillment of the raw materials industry, local wisdom and enciptaan ground work for the community around the forests